2019
DOI: 10.1016/j.cemconres.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supercritical carbonation on the strength and heavy metal retention of cement-solidified fly ash

Abstract: 13This paper presents both experimental and multi-physics studies on the carbonation and heavy 14 metal retention properties of cement-solidified fly ashes. Cement-solidified fly ash samples 15 with 40% and 60% fly ash ratios were tested for carbonation depth after being supercritically 16 carbonated. Tests were also carried out for compressive strength and retention capacity of heavy 17 metals of the samples before and after supercritical carbonation. Using CO2 absorption instead 18 of calcium carbonate to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Moreover, it was found that the box dimension declined when the carbonation depth increased, indicating that the data of compressive strength were increasingly centralized. Therefore, it was concluded that carbonation-induced corrosion can result in the decrease of compressive strength of concrete, in agreement with conclusion Zha [35].…”
Section: Range Of Carbonation Depth (Mpa)supporting
confidence: 86%
“…Moreover, it was found that the box dimension declined when the carbonation depth increased, indicating that the data of compressive strength were increasingly centralized. Therefore, it was concluded that carbonation-induced corrosion can result in the decrease of compressive strength of concrete, in agreement with conclusion Zha [35].…”
Section: Range Of Carbonation Depth (Mpa)supporting
confidence: 86%
“…In addition, it is known that the carbonation depth increased with the increase of time. Therefore, combined with the definition of carbonation depth, it was concluded that carbonation-induced corrosion can result in the decrease of compressive strength of concrete, which agrees with the conclusion drawn from Zha [40].…”
Section: Prediction For the Mean Value Of Compressive Strengthsupporting
confidence: 84%
“…On the basis of the building code calibration, concrete quality is determined by the guaranteed rate of above 95% [40]. Therefore, to evaluate concrete failure time based on reliability, the guaranteed rate was applied in this paper.…”
Section: Concrete Guaranteed Rate and Concrete Failure Timementioning
confidence: 99%
“…Supercritical carbonation can accelerate the study of the aging characteristics of solidified products [90]. Zha et al [91] used a CO 2 closed-cycle system [92] to study the heavy metal leaching characteristics of supercritical carbonated cement product, and found that supercritical carbonation promoted the leaching of Cu and Pb.…”
Section: Principle Of Cement Solidification Methodsmentioning
confidence: 99%
“…In addition, the aging and carbonation of solidification products resulted in an increasing amount of calcium carbonate in the voids of the cement. The generated calcium carbonate exceeded the limit of the pores, which caused additional internal pressure and micro-cracks, thereby reducing the mechanical strength of the cement product [91]. It is evident that the cement solidified product of MSWI fly ash can only be used as a low-strength road basement, and base construction material [99].…”
Section: Effect Of Cement Solidification Of Fly Ash On the Mechanicalmentioning
confidence: 99%